Piperacillin-Tazobactam: an update for clinical use - R. Correa e Castro Costa, Alice; Gomes, Andréia Patrícia; V. Varejão, Eduardo Vinícius; Brunes, Romario; Tavares, Walter; Santana, Luiz Alberto; Siqueira-Batista, Rodrigo (Brazilian Journal of Health and Biomedical Sciences, 2024)
Introduction: Piperacillin-tazobactam, a broad-spectrum penicillin, is an important option in the treatment of infections, especially in critically ill patients who exhibit high rates of resistance to various antimicrobial agents. Understanding this medication and updates on its clinical use is of paramount significance to guide precise therapeutic choices aimed at the optimization of patient care. Objective: To describe the main pharmacological and therapeutic aspects of piperacillin-tazobactam, highlighting its clinical application and updates related to its use. Methods: A narrative review of the literature was conducted in order to provide an update on the most relevant aspects related to piperacillin-tazobactam, including (1) a brief history; (2) chemical structure; (3) mechanism of action; (4) resistance mechanisms; (5) spectrum; (6) major clinical uses; and (7) adverse effects. Results: The safe use of piperacillin-tazobactam requires rapid testing for antimicrobial resistance patterns, thus discouraging its empirical use in cases of ESBL-producing microorganisms. In patients undergoing renal replacement therapy, antibiotic goals must be established promptly. For critically ill patients, monitoring pharmacodynamic and pharmacokinetic variability is essential. Conclusion: Piperacillin-tazobactam remains a vital drug in the management of critically ill patients, while requiring constant updates. In addition, further studies are required, especially concerning its continuous use and the selection of alternatives to carbapenem-resistant medications.